Bioactive Compounds of Fresh and Dried Pleurotus ostreatus Mushroom - Mohamed, Eman Mostafa; Farghaly, Fatma Ali (International Journal of Biotechnology for Wellness Industries, 2014)
Chemical composition of the fresh and dried mushroom Pleurotus ostreatus and their bioactive secondary metabolic products were studied. The ethanolic extracts of the P. ostreatus cultivated on rice straw supplemented by wheat bran were studied by Gas Chromatography/Mass Spectrometry (GC/MS) analysis. A total of hundred and seven metabolites were detected in tested samples. These include 56 metabolites only detected in fresh sample, 37 metabolites only detected in dry sample, and 14 metabolites were detected in the both samples. The detected metabolites could be classified into nine chemical groups including 2 metabolites related to acids, 5 alcohols, 27 alkane, 3 amides, 27 esters, 8 fatty acids, 4 terpenoids, 29 heterocyclic and 2 phenols. The bioactivity of the metabolic products could be classified: anticholesterol, anticancer and essential fatty acids which support human health. On comparison between fresh and dried P. ostreatus samples, we found that the high number of metabolites was recorded in the fresh extract. Fifty five aroma compounds were recorded and including (27 esters, 9 ketones, 7 thiols, 5 alcholos, 4 terpenoids, 2 phenols and 1 aldehyde). The selenium content in P. ostreatus samples was measured by using ACAL –APR -51-00 test methods and showed that the fresh sample has 58.24 mg/kg but the dry sample has 100.31 mg/kg.